Assessing the Scale and Pace of Large Shell-Bearing Site Occupation in the Prince Rupert Harbour Area, British Columbia. (3rd April 2019) - Letham, Bryn; Martindale, Andrew; Supernant, Kisha; Brown, Thomas J.; Cybulski, Jerome S.; Ames, Kenneth M.
ABSTRACT: Methodological advancements in geoarchaeology and spatial and chronological modeling are opening new avenues to interpreting large coastal shell-bearing sites. We document the developmental histories of two such sites around Prince Rupert Harbour, Canada, using systematic percussion coring, intensive radiocarbon dating, and 3D surface mapping with Total Station and LiDAR. We also re-analyze a third site (Boardwalk/GbTo-31) excavated and radiocarbon dated in the 1960s, 1970s, and early 2000s using archival field notes, site maps, and stratigraphic profiles georectified using LiDAR. We map the natural landform beneath the sites and document the degree to which people physically modified landforms through the deposition of massive shell accumulations. We model site development through time and space and use accumulation rates and OxCal modeling to test for intentional deposition events. All three sites demonstrate complex and heterogeneous occupation histories. At each we identify instances of very rapid deposition that effectively terraced and extended parts of the natural landform to create places for constructing houses, though these episodes take place within longer histories of slower quotidian deposition. The anthropogenic modifications to the coastline in this area are the result of these mixed processes associated with long histories of occupation.